Education for people and planet creating sustainable futures for all. - Unesco (Paris Unesco, 2016)
"Education for People and Planet: Creating Sustainable Futures for All explores the complex relationship between education and the new 2030 Agenda for Sustainable Development, covering six fundamental pillars - Planet, Prosperity, People, Peace, Place and Partnerships. This report shows that education will not deliver its full potential unless participation rates increase dramatically and sustainable development guides education system reform. It also warns of the destructive impact that climate change, conflict, unsustainable consumption and the increasing gap between rich and poor have on education. A huge transformation is needed if we are to create sustainable futures for all. This edition of the Global Education Monitoring Report (GEM Report) is the first in a series that will assess the progress of education under the new Sustainable Development Goals (SDGs). The GEM Report provides evidence-based recommendations on the policies, strategies and programmes needed to meet the ambitious Education 2030 vision. It discusses the challenges of monitoring progress on the new global education goal and targets to ensure improvement in access, participation, completion, learning and reduced inequality. It provides readers with an authoritative source to enable them to argue for the value and importance of education at all levels of decision-making."--Back cover.
Includes bibliographical references and index.
Also available via the Internet.
Keywords: Educational change; Educational planning; Education and state; International education; Education -- Monitoring; Political planning; Sustainable development